Implementation of digital twins in the process industry: A systematic literature review of enablers and barriers - Perno, Matteo; Hvam, Lars; Haug, Anders (Computers in industry, 2022)
•Literature on digital twins in the process industry is fragmented and immature.•There is a lack of common understanding of what digital twins are.•Challenges to digital twin implementation are identified and categorized.•Enablers to digital twin implementation are identified and categorized.•A model connecting barriers and enablers for implementing digital twins is introduced. Since the introduction of the concept of “digital twins” (DTs) in 2002, the number of practical applications in different industrial sectors has grown rapidly. Despite the hype surrounding this technology, companies face significant challenges upon deciding to implement DTs in their organizations due to the novelty of the concept. Furthermore, little research on DT has been conducted for the process industry, which may be explained by the high complexity of accurately representing and modeling the physics behind production processes. To consolidate the fragmented literature on the enabling factors and challenges in DT implementation in the process industry, this study organizes the existing studies on DTs with a focus on barriers and enablers. On this basis, this study contributes to the existing body of knowledge on DTs by organizing the DT literature and by proposing conceptual models describing enablers of and barriers to DT implementation, as well as their mutual relationships.